The mgtCBR mRNA Leader Secures Growth of Salmonella in Both Host and Non-host Environments - Park, Myungseo; Kim, Hyunkeun; Nam, Daesil; Kweon, Dae-Hyuk; Shin, Dongwoo (Frontiers in Microbiology, 2019)
Upon intracellular cues, bacterial mRNA leaders often form secondary structures that determine expression of a downstream protein-coding region(s), thereby providing bacteria with a mechanism to control the amounts of necessary proteins in the right locales. Here we describe a polycistronic mRNA leader that secures bacterial growth by preventing dysregulated expression of the protein-coding regions. In Salmonella, the mgtCBR mRNA encodes the virulence protein MgtC and the Mg2+ transporter MgtB. A mutant designed to produce leaderless mgtCBR mRNA induced MgtC and MgtB in conditions that promote mgtC transcription. The dysregulated expression of MgtC and MgtB impaired bacterial growth under all such non-host environments. While MgtC, but not MgtB, normally reduces ATP levels in a process requiring the F1Fo ATP synthase, dysregulated MgtC and MgtB reduced ATP levels independently of the F1Fo ATP synthase, which correlated with the mutant’s growth defect. The mutant showed dysregulated MgtC expression and attenuated survival inside macrophages. While MgtB normally does not affect the phenotype, MgtB impaired intramacrophage survival of the mutant in the presence of MgtC. We provide an example showing that a polycistronic mRNA leader prevents the dysregulated function of protein-coding regions to allow bacteria to proliferate across complex niches.